1998
DOI: 10.1046/j.1471-4159.1998.71041676.x
|View full text |Cite
|
Sign up to set email alerts
|

7Li Nuclear Magnetic Resonance Study for the Determination of Li+ Properties in Neuroblastoma SH‐SY5Y Cells

Abstract: Lithium has been used clinically in the treatment of manic depression. However, its pharmacologic mode of action remains unclear. Characteristics of Li ± interactions in red blood cells (RBCs) have been identified. We investigated Li + interactions on human neuroblastoma SH-SY5Y cells by developing a novel 7Li NMR method that provided a clear estimation of the intra-and extracellular amounts of LV in the presence of the shift reagent thulium-1,4,7,10tetrazacyclododecane-N , N', N", N"-tetramethylene phosphonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(48 citation statements)
references
References 22 publications
2
46
0
Order By: Relevance
“…Repeat T 2 measurements separated by 10 days in four rats detected no individual change with time. Consistent with the above in vivo results, Nikolakopoulos et al 42 found T 1 and T 2 values of 5.1 s and 50 ms, respectively, for 7 Li in cultured neuroblastoma SH-SY5Y cells.…”
Section: Spin Relaxationsupporting
confidence: 69%
See 1 more Smart Citation
“…Repeat T 2 measurements separated by 10 days in four rats detected no individual change with time. Consistent with the above in vivo results, Nikolakopoulos et al 42 found T 1 and T 2 values of 5.1 s and 50 ms, respectively, for 7 Li in cultured neuroblastoma SH-SY5Y cells.…”
Section: Spin Relaxationsupporting
confidence: 69%
“…Mota de Freitas and coworkers 42 have continued their work on neuroblastoma SH-SY5Y cells as a CNS model. Figure 3 shows 7 Li NMR spectra of Li influx and efflux for perfused neuroblastoma SH-SY5Y cells in agarose threads in the presence of HTmDOTP 4À shift reagent.…”
Section: Cns Modelsmentioning
confidence: 99%
“…countertransport (for both phloretin and HMA) pathways, respectively [10,18]. The Na þ channel activator, veratridine (at 0.50 mmol/L), was also tested in these transport experiments [10].…”
Section: Characterization Of LI þ Transport Pathways In Lymphoblastommentioning
confidence: 99%
“…The Na þ channel activator, veratridine (at 0.50 mmol/L), was also tested in these transport experiments [10].…”
Section: Characterization Of LI þ Transport Pathways In Lymphoblastommentioning
confidence: 99%
See 1 more Smart Citation